2014
DOI: 10.1063/1.4905191
|View full text |Cite
|
Sign up to set email alerts
|

Temporally and spatially resolved photoluminescence investigation of (112¯2) semi-polar InGaN/GaN multiple quantum wells grown on nanorod templates

Abstract: By means of time-resolved photoluminescence (PL) and confocal PL measurements, temporally and spatially resolved optical properties have been investigated on a number of InxGa1−xN/GaN multiple-quantum-well (MQW) structures with a wide range of indium content alloys from 13% to 35% on (112¯2) semi-polar GaN with high crystal quality, obtained through overgrowth on nanorod templates. With increasing indium content, the radiative recombination lifetime initially increases as expected, but decreases if the indium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 23 publications
(28 reference statements)
1
15
0
Order By: Relevance
“…Subsequently five periods of InGaN/GaN quantum wells (QWs) were grown with 10 nm thick GaN barriers and 2.2 nm thick InGaN wells with an 18% InN content. 19,20 The amber-emitting LEDs started with a 1.3 lm layer of GaN grown on top of a HT AlN buffer layer. Deposition of a layer of SiO 2 followed, which was patterned into a regular array of disks using standard lithography.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently five periods of InGaN/GaN quantum wells (QWs) were grown with 10 nm thick GaN barriers and 2.2 nm thick InGaN wells with an 18% InN content. 19,20 The amber-emitting LEDs started with a 1.3 lm layer of GaN grown on top of a HT AlN buffer layer. Deposition of a layer of SiO 2 followed, which was patterned into a regular array of disks using standard lithography.…”
Section: Methodsmentioning
confidence: 99%
“…The TR-PL decay curves were acquired at room temperature for all the samples, and the results are shown in Figure 4. A standard two-exponential-component model was used to study the decay dynamics, and the decay [23], where I(t) is the PL intensity as a function of time, A 1 and A 2 are constants, and τ 1 and τ 2 represent fast and slow decay lifetime, respectively. The fast decay lifetime corresponds to the rapid carrier recombination in MQWs, which is determined by both radiative and non-radiative recombination processes [24].…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…28,31 The strong ELOC in m-plane MQW 18 and the (11 22) MQW samples studied here can be another reason that should be taken into account with the reduced polarization fields 4,5 to explain why non-/semi-polar MQW structures have a much shorter radiative lifetime compared to polar MQW. 4,[12][13][14]20 To investigate the Stokes-shift of the samples, PL spectra together with PLE absorption edge were measured at 10 K using the Xe-lamp excitation source (P ex $ 10 -5 W/cm 2 ). The PLE measurements were performed with a detection energy fixed at each MQW peak emission energy.…”
Section: Resultsmentioning
confidence: 99%
“…16,17 It should be noted that the ELOC intrinsically exists in InGaN alloys, irrespective of growth orientation employed. 2,3,11,[13][14][15][18][19][20][21] Zhang et al 14 have reported that (11 22) QWs exhibit larger localization depths than polar QWs (estimated from TR-PL measurements at 7 K). Recently, by temperature-dependent photoluminescence (TD-PL) measurements, a strong ELOC degree has been found in (11 22) In 0.2 Ga 0.8 N QWs that causes a blue-shift of the QW exciton emission with rising temperature from $200 K to 340 K, irrespective of excitation source used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation